Stef Soto, Taco Queen - Torres, Jennifer 1980- (New York : Little, Brown and Company, 2017)
"Mexican-American Stef Soto is hoping to break free from her overprotective parents and embarrassing reputation from her family's taco truck business, but she soon learns that family, friendship, and the taco truck are important and wonderful parts of her life"--
Keywords: Families -- Juvenile fiction; Food trucks -- Juvenile fiction; Tacos -- Juvenile fiction; Friendship in children -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Family life -- Fiction; Food trucks -- Fiction; Tacos -- Fiction; Friendship -- Fiction; Mexican Americans -- Fiction